2019
DOI: 10.1021/acsbiomaterials.9b00532
|View full text |Cite
|
Sign up to set email alerts
|

Smart Microneedle Fabricated with Silk Fibroin Combined Semi-interpenetrating Network Hydrogel for Glucose-Responsive Insulin Delivery

Abstract: Microneedle (MN) technology, which can transdermally deliver insulin in a noninvasive manner, offers a promising way to replace subcutaneous self-injection for diabetes management. Hydrogel is an attractive candidate for MN fabrication because of its biocompatibility, controllable degradability, and possibility to achieve sustained as well as stimuli-responsive drug delivery. Herein, we report a smart MN composed of a semi-interpenetrating network (semi-IPN) hydrogel prepared by biocompatible silk fibroin (SF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 51 publications
0
66
0
Order By: Relevance
“…For instance, non-degradable MNs were constructed from hydrogel containing phenylboronic acid (PBA) as a glucose-sensitive agent. The results exhibited not only that insulin release depended on BGLs, but they also showed the stability and shape preservation after 7 days in aqueous solution, which demonstrated their capability for long-term, on-demand insulin release [132].…”
Section: Bio-responsive Mnsmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, non-degradable MNs were constructed from hydrogel containing phenylboronic acid (PBA) as a glucose-sensitive agent. The results exhibited not only that insulin release depended on BGLs, but they also showed the stability and shape preservation after 7 days in aqueous solution, which demonstrated their capability for long-term, on-demand insulin release [132].…”
Section: Bio-responsive Mnsmentioning
confidence: 86%
“…material and lead to insulin release [132]. In another study, insulin loaded mesoporous bioactive glasses (MBGs) containing GOx were capped by ZnO quantum dots (ZnO QDs).…”
Section: Bio-responsive Mnsmentioning
confidence: 99%
“…In an in vitro release experiment, the hydrogel microneedles were found to provide quick insulin delivery in response to a change in the glucose level and offered sustained insulin release in a noninvasive manner over a reaction time of ≈8 h at pH 7.4, 37°C. [218] Glucose-responsive hydrogels have also been applied for the controlled delivery of other (model) drug molecules rather than insulin. For example, Li et al prepared a glucose-responsive hydrogel made of phenylboronic-modified chitosan and oxidized dextran (OD).…”
Section: Enzyme-and Glucose-responsive Injectable Hydrogels For Contrmentioning
confidence: 99%
“…Developing smart MNs in response to external environmental change in a long-acting way is of vast demand. Chen et al reported a nondegradable, hydrogel-forming MN composed of a semi-interpenetrating network hydrogel for glucose-responsive insulin delivery in a painless, convenient, and safe manner [145]. The needle region was formed by glucose-responsive silk fibroin and phenylboronic acid/acrylamide.…”
Section: Drug Deliverymentioning
confidence: 99%